PENGARUH NON-PERFORMING FINANCING (NPF) TERHADAP RETURN ON ASSETS (ROA) - Zuraidah; Nur Koriatus Sholikhah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2018)
Non Performance Financing (NPF) is defined as a loan that has difficulty repaying due to intentional factors and or due to external factors beyond the ability of the debtor which can be measured by its collectability. Return on Assets (ROA) is the ratio ability used to measure management ability to generate income from asset management. This study aims to find out how the influence of NPF on ROA in Islamic People's Financing Banks in East Java in 2013-2016. This research was carried out on the BPRS in East Java using a quantitative approach. The sampling technique used in this study was through a purposive sampling approach. The sample of this study was 125 of the number of BPRS that experienced problems in the field of problematic financing and high ROA. The results of this study indicate that there is no significant relationship between Non Performance Financing (NPF) on Return on Assets (ROA) on BPRS in East Java in 2013-2016. This can be seen from the significance of the t test both of which is tcount 1.295 <t table 1.65909 which means that Ho is accepted and Ha is rejected. Besides, the regression test results show that 2.4% Non Performance Financing (NPF) on BPRS in East Java is affected by (ROA). The constant value in the regression test of 0.275 states that if there is no Non Performance Financing (NPF) worth 0, then Return on Assets (ROA) is 27.5%. While the regression coefficient 0.175 states that every addition of 1% NPF will increase ROA by 17.5%. The insignificance is because the value of the reserve allocated for problem financing is greater than the value of the problematic financing faced. This proves that high Non-Performance Financing (NPF) has no significant effect on Return on Assets (ROA) on BPRS in East Java.